2009
DOI: 10.1364/oe.17.000872
|View full text |Cite
|
Sign up to set email alerts
|

Channel coding and time-diversity for optical wireless links

Abstract: Atmospheric turbulence can cause a significant performance degradation in free space optical communication systems. An efficient solution could be to exploit the temporal diversity to improve the performance of the transmission link. Depending on the tolerable delay latency, we can benefit from some degree of time diversity that we can exploit by employing channel coding and interleaving. In this paper, we investigate the efficiency of several channel coding techniques for different time diversity orders and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 23 publications
0
70
0
6
Order By: Relevance
“…In this way, it can be shown that BER optimization provides numerical results for the normalized beamwidth ω z /r following a linear performance for each value of distance, where its corresponding slope is subject to the turbulence conditions. This leads to easily obtain a first-degree polynomial given by ω z /r optimum ≈ −0.034β 2 + 0.72β + 2.15 σ s /r, (25) where the slope follows a quadratic form in β [11]. The use of this expression is also shown in Fig.…”
Section: Advances In Optical Communication 202mentioning
confidence: 97%
See 1 more Smart Citation
“…In this way, it can be shown that BER optimization provides numerical results for the normalized beamwidth ω z /r following a linear performance for each value of distance, where its corresponding slope is subject to the turbulence conditions. This leads to easily obtain a first-degree polynomial given by ω z /r optimum ≈ −0.034β 2 + 0.72β + 2.15 σ s /r, (25) where the slope follows a quadratic form in β [11]. The use of this expression is also shown in Fig.…”
Section: Advances In Optical Communication 202mentioning
confidence: 97%
“…This temporal correlation can be overcome by means of long interleavers, being usually assumed both in the analysis from the point of view of information theory and error rate performance analysis of coded FSO links [4,5,24]. However, as in [22,25], we here assume that the interleaver depth can not be infinite and, hence, we can potentially benefit from a degree of time diversity limited equal to 2. This consideration is justified from the fact that the latency introduced by the interleaver is not an inconvenience for the required application.…”
Section: System and Channel Modelmentioning
confidence: 99%
“…This temporal correlation can be overcome by means of long interleavers, being usually assumed both in the analysis from the point of view of information theory and error rate performance analysis of coded FSO links [4,37,45]. However, as in [48], we here assume that the interleaver depth can not be infinite and, hence, we can potentially benefit from a degree of time diversity limited equal to TDO. This consideration is justified from the fact that the latency introduced by the interleaver is not an inconvenience for the required application.…”
Section: System and Channel Modelmentioning
confidence: 99%
“…For the sake of simplicity, we here consider values multiples of 2 for RR when rate reduction is applied, i.e RR = {1, 2, 4, 8, ···} as well as for the time-diversity order effective TDO which is provided by interleaving, i.e. TDO = {1, 2, 4}, in this fashion, allowing to satisfy different latency requirements in the system [48].…”
Section: Proposed Rate-adaptive Transmission Schemementioning
confidence: 99%
“…Another promising solution is the use of diversity techniques and the most popular scheme is the spatial diversity, i.e., the employment of multiple transmit/receive apertures, a well known diversity technique in Radio-Frequency (RF) systems [46,48,49,61,69,72,78,80]. By using multiple apertures at the transmitter and/or the receiver, the inherent redundancy of spatial diversity has the potential to significantly enhance the performance.…”
Section: Introductionmentioning
confidence: 99%